KARAKTERISTIK KEKUATAN BENDING DAN KEKUATAN TEKAN KOMPOSIT SERAT HYBRID KAPAS/GELAS SEBAGAI PENGGANTI PRODUK KAYU - Harsi, Harsi; Sari, Nazmi Herlina; Sinarep, Sinarep (Dinamika Teknik Mesin, 2015)
Wood material is very popular in indonesia and all over the world, there are so many people who use it as their buildings contruction and also for their home tools, because the wood material is strong, long lasting, green living, save and lux. On the other hand the wood material will be mouldy if it meets water, thats why this material is not suitable to be placed in humid or wet places we need a new material that can be used as the subtitution of the wood material. The aim of this research is to know about how to make the composite of cotton/glass hybrid fiber and its mecanical using epoxy matrix, and then compare it with wood product. The wood product that used in this research is mahoni.The composite making is using hand lay-up method and the variety fraction volume of cotton fiber and glass fiber are : 30% : 0%, 25% : 5%, 20% : 10%, 15% : 15%, 10% : 20%, 5% : 25%, 0% : 30 %, the epoxy matrix volume fraction is 70 %, where the orientasion of cotton fiber is rondom and 2 cm in lenght, whereas the orientasion of the glass fiber is equally with fiber lenght up to the lenght of mould. The researcher did some test they are: bending test that based on ASTM D 790 standart, compression test that based on ASTM D 695 standart.The bending strenght’s mean of all volume fraction’s varieties of cotton/glass hybrid fiber composite shows the higher bending strenght than the bending strenght of mahoni which is used as the comparator. Afterwards the pressing strenght’s mean of cotton/glass hybrid fiber composite especially in  20%:10% and 0%:30% fraction volume varieties, which is have the values orderly 37,74 MPa and 47,53 MPa, and it shows the higher pressing strenght than the pressing strenght of mahoni, it is 36,78 MPa. Based on the recearch that have been done we can conclude that the characteristic of mechamical cotton/glass hybrid fiber composite can be used as the (alternative) wood subtitution especially mahoni.